Crystal form of compound YZG-331 and preparation method thereof
By screening and verifying the multiple crystal forms of YZG-331, the problem of incompletely proving the crystal forms of the drug is solved, and new crystal forms are provided, which improves the stability and development potential of the drug.
Patent Information
- Application Number
- CN202410057033.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-01-15
AI Technical Summary
In the prior art, the crystal form of the sedative hypnosis candidate drug YZG-331 has not been fully discovered, which affects its subsequent development and application.
Through various experimental techniques, the three crystal forms of YZG-331, including crystal forms A, B and A1, were screened and verified, and the corresponding preparation methods were prepared.
It laid the foundation for the subsequent development of YZG-331, provided new crystal form options, and improved the stability and application potential of the drug.
Smart Images

Figure CN119798352A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of pharmaceutical crystal technology, and in particular to a new crystal form of compound YZG-331 and a preparation method thereof. Background Art
[0002] Considering the traditional application of Chinese medicines such as Gastrodia elata, which is mainly based on water decoction, the project team carried out research on water extracts of Gastrodia elata, from which a series of p-hydroxybenzyl alcohol phenols, p-hydroxybenzyl alcohol glycosides and citrate benzyl ester glycosides have been separated and identified [1-10], and a trace component N 6 -(p-Hydroxybenzyl)-adenosine (NHBA), with a yield of about 4 parts per 100,000, has a very significant sedative effect. When administered intraperitoneally, its sedative effect is more than a thousand times that of ingredients such as gastrodin [11,12]. Given the low oral bioavailability of NHBA (the effective dose of oral administration differs by more than 200 times from that of intraperitoneal injection), we confirmed that NHBA is the key active ingredient of the sedative and hypnotic effect of Gastrodia elata, and further conducted repeated synthesis and drug efficacy, preliminary drug metabolism and toxicity tests and other drugability evaluations, and finally obtained the sedative and hypnotic candidate drug YZG-331, and conducted a series of studies on N containing YZG-331 and its analogs. 6 -Adenosine derivatives and N 6 -Substituted purine derivatives, their preparation methods, pharmaceutical compositions and uses, as well as their tablet dosage forms and preparation methods have been patented [13-17] and have been successively granted Chinese and American patents. In order to investigate the potential crystal forms of YZG-331, a polymorph screening experiment was carried out and three crystal forms of YZG-331 were obtained.
[0003] References:
[0004] 1. Wang Yanan. Study on chemical components and biological activities of Gastrodia elata[D]. Peking Union Medical College, 2012.
[0005] 2. Guo Qinglan. Study on chemical components and biological activities of Gastrodia elata[D]. Peking Union Medical College, 2014.
[0006] 3. Zhou Xue. Study on chemical components of water extract of Gastrodia elata[D]. Peking Union Medical College, 2017.
[0007] 4. Wang Yanan, Lin Sheng, Chen Minghua, et al. Chemical components of water extract of Gastrodia elata[J]. Chinese Journal of Traditional Chinese Medicine 2012, 37: 1775. 5. Guo QL; Wang YN; Zhu CG; et al. 4-Hydroxybenzyl-substitutedglutathione derivativesfrom Gastrodia elata[J]. J. Asian Nat. Prod. Res. 2015, 17: 439.
[0008] 6.Guo Q.; Wang Y.; Lin S.; et al.4-Hydroxybenzyl-substituted amino acidderivatives from
[0009] Gastrodia elata[J].Acta Pharm.Sin.B 2015,5:350.
[0010] 7. Guo QL; Lin S.; Wang YN; et al. Gastrolatathioneine, an unusualergothioneine derivative from an aqueous extract of “tian ma”: A natural product co-produced by plant and symbioticfungus. Chin. Chem. Lett. 2016, 27: 1577.
[0011] 8.Zhou
[0012] Chin.Chem.Lett.2017,28:1185.
[0013] 9.Xu CB; Guo QL; Wang YN; et al.Gastrodin derivatives from Gastrodia elata[J].Nat.Prod.
[0014] Bioprospect.2019,9:393.
[0015] 10.Wang Y.; Zhang M.; Zhou X.; et al. Insight into medicinal chemistry behind traditional Chinese medicines: p-hydroxybenzyl alcohol-derived dimers and trimers from Gastrodia elata[J].Nat.
[0016] Prod.Bioprospect.2021,11:31.
[0017] 11. Zhang Y.; Li M.; Kang RX; at al.NHBA isolated from Gastrodia elataexerts sedative and hypnotic effects in sodium pentobarbital-treated mice[J].Pharm.Biochem.Behav.2012,102:450.
[0018] 12.He J.; Luo Z.; Huang L.; et al.Ambient mass spectrometry imagingmetabolomics method provides novel insights into the action mechanism of drugcandidates[J]. Anal.Chem.2015,87:5372.
[0019] 13. Shi Jiangong, Zhang Jianjun, Yue Zhenggang, et al. 6 -substituted adenosine derivatives and N 6 -Substituted adenine derivatives and their uses [P]. ZL200980162826.5.
[0020] 14. Zhang Jianjun, Shi Jiangong, Li Min, et al. 6 -Substituted adenosine derivatives, their preparation methods, pharmaceutical compositions and uses [p]. ZL 200810114594.3.
[0021] 15. Shi Jiangong, Zhang Jianjun, Yue Zhenggang, et al. 6 -substituted adenosine derivatives and N 6-Substituted adenine derivatives and their uses[p].ZL201410539423.0.
[0022] 16.Shi Jiangong,Zhang Jianjun,Yue Zhenggang,et al.N 6 -substitutedadenosine derivatives and N 6 -sustituted adenine derivatives and uses thereof[p].US10174033 B2.
[0023] 17. Shi Jiangong, Zhang Jianjun, Zheng Wensheng, et al. A tablet for treating insomnia and its preparation method [p]. 2023112793499. Summary of the invention
[0024] The technical problem solved by the present invention is to provide a crystal form of compound YZG-331 as shown in the following formula and a preparation method thereof.
[0025]
[0026] In order to solve the technical problem of the present invention, the present invention provides a crystalline form A of compound YZG-331.
[0027] Using Cu-Kα radiation, the X-ray powder diffraction of the crystalline form A has characteristic peaks at diffraction angles 2θ of 17.4°±0.2°, 14.1°±0.2°, and 8.4°±0.2°.
[0028] Furthermore, the X-ray powder diffraction of the crystalline form A has characteristic peaks at one, two or three of the diffraction angles 2θ of 18.2°±0.2°, 12.5°±0.2°, and 13.1°±0.2°.
[0029] Furthermore, the X-ray powder diffraction of the crystal form A has characteristic peaks at one, two or three of the diffraction angles 2θ of 23.7°±0.2°, 24.4°±0.2°, and 6.6°±0.2°.
[0030] In a preferred embodiment, the X-ray powder diffraction of the crystalline form A has characteristic peaks at diffraction angles 2θ of 17.4°±0.2°, 14.1°±0.2°, 8.4°±0.2°, 18.2°±0.2°, 12.5°±0.2°, 13.1°±0.2°, 23.7°±0.2°, 24.4°±0.2°, and 6.6°±0.2°.
[0031] In a further preferred embodiment, the X-ray powder diffraction pattern of the crystalline form A has characteristic peaks and d values and relative intensities at the following positions of diffraction angle 2θ:
[0032]
[0033]
[0034] The crystal form A provided by the present invention is characterized in that its X-ray powder diffraction pattern is substantially as shown in the attached Figure 1 shown.
[0035] When differential scanning calorimetry analysis was performed, Form A showed an endothermic signal when heated to around 66°C and began to melt when heated to around 102°C. Figure 2 shown.
[0036] When thermogravimetric analysis was performed, Form A had a mass loss gradient of about 2.3% when heated to 100°C. Figure 3 shown.
[0037] According to the purpose of the present invention, the present invention provides a crystalline form B of compound YZG-331.
[0038] Using Cu-Kα radiation, the X-ray powder diffraction of the crystalline form B has characteristic peaks at diffraction angles 2θ of 6.1°±0.2°, 12.2°±0.2°, and 13.7°±0.2°.
[0039] Furthermore, the X-ray powder diffraction of the crystalline form B has characteristic peaks at one, two or three of the diffraction angles 2θ of 13.3°±0.2°, 17.6°±0.2°, and 6.6°±0.2°.
[0040] Furthermore, the X-ray powder diffraction of the crystalline form B has characteristic peaks at one, two or three of the diffraction angles 2θ of 12.6°±0.2°, 23.9°±0.2°, and 8.0°±0.2°.
[0041] In a preferred embodiment, the X-ray powder diffraction of the crystalline form B has characteristic peaks at diffraction angles 2θ of 6.1°±0.2°, 12.2°±0.2°, 13.7°±0.2°, 13.3°±0.2°, 17.6°±0.2°, 6.6°±0.2°, 12.6°±0.2°, 23.9°±0.2°, and 8.0°±0.2°.
[0042] In a further preferred embodiment, the X-ray powder diffraction pattern of the crystalline form B has characteristic peaks and d values and relative intensities at the following positions of diffraction angle 2θ:
[0043] Diffraction angle 2θ d value Relative Strength % 6.1 14.5 100.0 6.6 13.4 56.5 8.0 11.0 27.4 12.2 7.3 62.2 12.6 7.0 56.3 13.3 6.7 57.1 13.7 6.5 59.2 17.6 5.1 57.0 23.9 3.7 28.0
[0044] The crystal form B provided by the present invention is characterized in that its X-ray powder diffraction pattern is substantially as shown in the attached Figure 4 shown.
[0045] When differential scanning calorimetry analysis was performed, Form B had an endothermic signal when heated to around 43°C and began to melt when heated to around 99°C. Figure 5 shown.
[0046] When thermogravimetric analysis was performed, Form B had a mass loss gradient of about 6.8% when heated to 120°C. Its TGA is shown in the attached Figure 6 shown.
[0047] According to the purpose of the present invention, the present invention provides a crystalline form A1 of compound YZG-331.
[0048] Using Cu-Kα radiation, the X-ray powder diffraction of the crystalline form A1 has characteristic peaks at diffraction angles 2θ of 11.6°±0.2°, 14.4°±0.2°, and 6.7°±0.2°.
[0049] Furthermore, the X-ray powder diffraction of the crystalline form A1 has characteristic peaks at one, two or three of the diffraction angles 2θ of 18.5°±0.2°, 20.8°±0.2°, and 12.8°±0.2°.
[0050] Furthermore, the X-ray powder diffraction of the crystalline form A1 has characteristic peaks at one, two or three of the diffraction angles 2θ of 8.6°±0.2°, 13.4°±0.2°, and 15.8°±0.2°.
[0051] In a preferred embodiment, the X-ray powder diffraction of the crystalline form A1 has characteristic peaks at diffraction angles 2θ of 11.6°±0.2°, 14.4°±0.2°, 6.7°±0.2°, 18.5°±0.2°, 20.8°±0.2°, 12.8°±0.2°, 8.6°±0.2°, 13.4°±0.2°, and 15.8°±0.2°.
[0052] In a further preferred embodiment, the X-ray powder diffraction pattern of the crystalline form A1 has characteristic peaks and d values and relative intensities at the following positions of diffraction angle 2θ:
[0053] Diffraction angle 2θ d value Relative Strength % 6.7 13.2 83.5 8.6 10.3 30.8 11.6 7.6 100.0 12.8 6.9 55.1 13.4 6.6 19.3 14.4 6.1 90.4 15.8 5.6 17.2 18.5 4.8 69.0 20.8 4.3 59.3
[0054] The crystal form A1 provided by the present invention is characterized in that its X-ray powder diffraction pattern is substantially as shown in the attached Figure 7 shown.
[0055] When differential scanning calorimetry analysis was performed, Form A1 had an endothermic signal when heated to around 51°C and began to melt when heated to around 97°C. Figure 8 shown.
[0056] When thermogravimetric analysis was performed, Form A1 had a mass loss gradient of about 6.7% when heated to 120°C. Its TGA is shown in the attached Fig. 9 shown.
[0057] Beneficial technical effects
[0058] The inventors of the present invention discovered three crystal forms of YZG-331 by using various experimental techniques in the process of studying the sedative and hypnotic candidate drug YZG-331, and verified the crystal form preparation method, which laid the foundation for the subsequent development of YZG-331. It is a new crystal form of the sedative and hypnotic candidate drug YZG-331. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 , X-ray powder diffraction pattern of Form A
[0060] Figure 2 , Differential scanning calorimetry (DSC) diagram of Form A
[0061] Figure 3 , Thermogravimetric analysis (TGA) of Form A
[0062] Figure 4 , X-ray powder diffraction pattern of Form B
[0063] Figure 5 , Differential scanning calorimetry (DSC) diagram of Form B
[0064] Figure 6 , Thermogravimetric analysis (TGA) of Form B
[0065] Figure 7 , X-ray powder diffraction pattern of Form A1
[0066] Figure 8 , Differential scanning calorimetry (DSC) diagram of Form A1
[0067] Fig. 9 , Thermogravimetric analysis (TGA) of Form A1
[0068] Fig.10 , Dynamic moisture adsorption-desorption (DVS) curve of Form A
[0069] Fig.11 , Dynamic moisture adsorption-desorption (DVS) curve of amorphous YZG-331 DETAILED DESCRIPTION
[0070] The present invention will be further described below through specific examples, but it is not intended to limit the scope of protection of the present invention. Those skilled in the art may make improvements to the preparation method and the apparatus used within the scope of the claims, and these improvements should also be regarded as the scope of protection of the present invention. Therefore, the scope of protection of the patent of the present invention shall be based on the attached claims.
[0071] The abbreviations used in the present invention are explained as follows:
[0072] XRPD: X-ray powder diffraction
[0073] DSC: Differential Scanning Calorimetry
[0074] TGA: Thermogravimetric analysis
[0075] DVS: Dynamic Water Sorption
[0076] The X-ray powder diffraction pattern of the present invention is obtained by PANalytical Empyrean or X'Pert 3 The X-ray powder diffractometer is used for the collection. The parameters of the X-ray powder diffraction method of the present invention are as follows:
[0077] X-ray source: Cu, Kα
[0078] 1.54060; 1.54439
[0079] Kα2 / Kα1 intensity ratio: 0.50
[0080] Voltage: 45 kV
[0081] Current: 40 milliamperes (mA)
[0082] Divergence slit: 1 / 8 degree
[0083] Scan mode: continuous scan
[0084] Scanning range: from 3.0 to 40.0 degrees
[0085] Scanning step: 0.0263 degrees
[0086] Scan time per step: 46.67 degrees
[0087] Scan time: about 5 minutes
[0088] The differential scanning calorimetry (DSC) graph of the present invention was collected on a TA Discovery 2500. The method parameters of the differential scanning calorimetry (DSC) of the present invention are as follows:
[0089] Method: Linear temperature ramp
[0090] Sample pan: Aluminum pan, open
[0091] Temperature range: room temperature to 350°C
[0092] Scan rate: 10℃ / min
[0093] Shielding gas: N2
[0094] The thermogravimetric analysis (TGA) graph of the present invention was collected on a TA Discovery 5500. The method parameters of the thermogravimetric analysis (TGA) of the present invention are as follows:
[0095] Method: Linear temperature ramp
[0096] Sample pan: Aluminum pan, pressure cover
[0097] Temperature range: room temperature to 300°C
[0098] Scan rate: 10℃ / min
[0099] Shielding gas: N2
[0100] The dynamic moisture adsorption graph of the present invention is collected on the DVS Intrinsic of SMS. The method parameters of the dynamic moisture adsorption of the present invention are as follows:
[0101] Temperature: 25℃
[0102] Sample size: 20 to 40 mg
[0103] Protective gas and flow rate: N2, 200 ml / min
[0104] Maximum mass change dm / dt at equilibrium: 0.002% / min
[0105] Minimum dm / dt balance time: 10 minutes
[0106] Maximum balancing time: 180 minutes
[0107] Humidity range: Room humidity to 95% RH to 0% RH to 95% RH
[0108] Humidity gradient: 10%RH (0%RH to 90%RH), 5%RH (90%RH to 95%RH)
[0109] The high performance liquid chromatography (HPLC) purity data in the present invention was collected from Agilent 1260, and the detector used was a diode array detector (DAD). The HPLC method parameters for testing purity described in the present invention are as follows:
[0110] 1. Chromatographic column: Zorbax Eclipse XDB-C18, 150×4.6mm, 5μm
[0111] 2. Mobile phase: A: 0.1% acetic acid aqueous solution
[0112] B: Methanol
[0113] The elution gradient is as follows:
[0114]
[0115]
[0116] 3. Flow rate: 0.8mL / min
[0117] 4. Injection volume: 2μL or 10μL
[0118] 5. Detection wavelength: 269nm
[0119] 6. Column temperature: 40℃
[0120] 7. Injector temperature: room temperature
[0121] 8. Diluent: 0.1% methanol / water (85:15, volume ratio) solution
[0122] Unless otherwise specified, the following examples were all operated at room temperature.
[0123] Example 1: Preparation of Form A
[0124] Using 6-chloroadenosine and (S)-α-ethylbenzylamine as starting materials and sodium carbonate as an acid capture agent, the mixture is refluxed in anhydrous ethanol, and after one-step reaction and recrystallization, compound YZG-331 can be obtained.
[0125] After testing, the solid obtained in this example is crystal form A. The X-ray powder diffraction data of the obtained solid are shown in Table 1. The above crystal form A sample was subjected to DSC and TGA tests. The data are as follows: Figure 2 and Figure 3 shown.
[0126] Table 1
[0127] Diffraction angle 2θ d value Relative Strength % 6.6 13.5 23.7 8.4 10.5 84.3 11.4 7.8 14.8 12.5 7.1 59.8 13.1 6.7 57.4 14.1 6.3 90.5 15.5 5.7 19.2 16.8 5.3 3.3 17.4 5.1 100.0 18.2 4.9 65.0 19.6 4.5 4.2 20.4 4.3 63.6 20.6 4.3 22.4 22.2 4.0 8.2 23.1 3.8 1.9 23.7 3.7 37.8 24.4 3.7 26.0 26.1 3.4 7.1 26.4 3.4 10.1 28.6 3.1 3.7 30.8 2.9 5.2 32.1 2.8 4.0
[0128] Example 2: Preparation of Form B
[0129] 21.1 mg of compound YZG-331 solid was weighed and placed in a 2 ml glass vial, and 0.5 ml of methyl tert-butyl ether was added to obtain a suspension. The suspension was magnetically stirred at 5° C. for about 4 days.
[0130] After testing, the solid obtained in this example is crystal form B. The X-ray powder diffraction data of the obtained solid are shown in Table 2. The above crystal form B sample was subjected to DSC and TGA tests. The data are as follows: Figure 5 and Figure 6 shown.
[0131] Table 2
[0132] Diffraction angle 2θ d value Relative Strength % 5.0 17.7 15.5 6.1 14.5 100.0 6.6 13.4 56.5 7.3 12.1 5.7 8.0 11.0 27.4 8.5 10.4 12.6 9.2 9.6 8.1 11.0 8.0 13.6 11.4 7.7 22.2 12.2 7.3 62.2 12.6 7.0 56.3 13.3 6.7 57.1 13.7 6.5 59.2 14.2 6.2 21.7 14.6 6.1 16.5 15.1 5.9 14.2 15.4 5.7 19.1 15.7 5.6 24.6 16.7 5.3 16.7 17.1 5.2 19.8 17.6 5.1 57.0 18.0 4.9 16.5 18.3 4.8 60.1 19.2 4.6 10.1 19.9 4.5 8.6 20.5 4.3 25.4 21.3 4.2 11.5 23.9 3.7 28.0
[0133] Example 3: Preparation of Form A1
[0134] Weigh 20.0 mg of compound YZG-331 and place it in a 3 ml glass vial. Pipette 4 ml of ethyl acetate into a 20 ml glass vial. Place the 3 ml glass vial containing the solid sample in a 20 ml glass vial with its lid open. Tighten the cap of the 20 ml glass vial and place it at room temperature for 10 days. Transfer the solid to room temperature and humidity for 1 day.
[0135] After testing, the solid obtained in this example is crystal form A1, and the X-ray powder diffraction data of the obtained solid are shown in Table 3. The above crystal form A1 sample was subjected to DSC and TGA tests, and the data are as follows: Figure 8 and Fig. 9 shown.
[0136] Table 3
[0137] Diffraction angle 2θ d value Relative Strength % 6.7 13.2 83.5 8.6 10.3 30.8 11.6 7.6 100.0 12.8 6.9 55.1 13.4 6.6 19.3 14.4 6.1 90.4 15.8 5.6 17.2 17.2 5.2 7.6 17.4 5.1 6.7 17.7 5.0 43.5 18.5 4.8 69.0 19.9 4.5 2.1 20.8 4.3 59.3 22.5 3.9 12.8 22.9 3.9 5.4 23.3 3.8 2.2 24.0 3.7 24.0 24.2 3.7 36.4 24.8 3.6 14.3 26.6 3.4 10.1 26.9 3.3 6.4 27.8 3.2 3.4 29.2 3.1 5.0 29.6 3.0 2.5 31.4 2.8 5.4 32.5 2.8 3.3 33.9 2.6 2.4 34.3 2.6 2.9 34.9 2.6 2.6
[0138] Examples 4-5: Preparation of Form A (Anti-solvent Addition Method)
[0139] Weigh about 20 mg of compound YZG-331 solid and place it in a 20 ml glass vial, add the corresponding volume of positive solvent, and use a polytetrafluoroethylene filter with a pore size of 0.45 microns to filter the sample solution into a new 20 ml glass vial. Then magnetically stir the obtained clear solution (speed of about 1000 rpm), and add the corresponding anti-solvent dropwise thereto. If solid precipitates, centrifuge the obtained solid. If it becomes oil, transfer to 5-50 ° C temperature cycle suspension stirring (procedure: 50 ° C constant temperature for 2 hours, 0.1 ° C / min rate down to 5 ° C, 5 ° C constant temperature for 2 hours, and then raise the temperature to 50 ° C after 0.5 hours. Perform 3 cycles in total, reduce to 5 ° C at a rate of 0.1 ° C / min and stir at 5 ° C).
[0140] The detailed experimental conditions involved in the above examples are shown in Table 4. After testing, the solids obtained in the above examples are all crystal form A. Taking Example 5 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 5.
[0141] Table 4
[0142]
[0143] Table 5
[0144] Diffraction angle 2θ d value Relative Strength % 6.6 13.4 100.0 8.5 10.4 24.3 11.4 7.8 75.2 12.6 7.0 61.6 13.2 6.7 27.7 14.2 6.2 79.0 15.7 5.7 12.8 17.0 5.2 6.3 17.4 5.1 74.1 18.2 4.9 75.3 20.5 4.3 76.9 22.5 3.9 9.7 23.5 3.8 10.5 23.8 3.7 54.9 24.4 3.6 28.4 26.2 3.4 7.2 26.5 3.4 10.9 27.0 3.3 2.7 27.8 3.2 2.0 28.9 3.1 5.6 29.4 3.0 2.6 30.9 2.9 8.4
[0145] Examples 6-8: Preparation of Form A (Gas-Solid Diffusion Method)
[0146] Weigh about 20 mg of compound YZG-331 solid and place it in a 3 ml glass vial. Pipette 4 ml of solvent into a 20 ml glass vial. Place the 3 ml glass vial containing the solid sample in the 20 ml glass vial with the lid open. Tighten the cap of the 20 ml glass vial and place it at room temperature.
[0147] The detailed experimental conditions involved in the above examples are shown in Table 6. After testing, the solids obtained in the above examples are all crystalline form A. Taking Example 7 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 7.
[0148] Table 6
[0149]
[0150] Table 7
[0151] Diffraction angle 2θ d value Relative Strength % 6.6 13.4 89.9 8.5 10.4 61.2 11.4 7.8 82.3 12.6 7.0 93.3 13.2 6.7 21.8 14.2 6.2 100.0 15.7 5.6 24.7 17.0 5.2 14.2 17.5 5.1 57.8 18.3 4.8 80.9 20.6 4.3 71.3 22.6 3.9 22.2 23.6 3.8 14.1 23.8 3.7 56.1 24.5 3.6 22.9 26.3 3.4 8.1 27.8 3.2 8.7 29.0 3.1 7.0 29.5 3.0 5.0 31.0 2.9 5.3 32.4 2.8 5.6 33.1 2.7 2.4 33.8 2.6 4.9 34.7 2.6 7.7
[0152] Example 9: Preparation of Form A (80°C Suspension Stirring Method)
[0153] 21.7 mg of compound YZG-331 solid was weighed and placed in a 2 ml glass vial, and 0.5 ml of m-xylene solvent was added to obtain a suspension. The suspension was magnetically stirred at 80° C. for about 4 days.
[0154] After testing, the solid obtained in the above example is Form A. The X-ray powder diffraction data of the obtained solid are shown in Table 8.
[0155] Table 8
[0156]
[0157]
[0158] Example 10: Preparation of Form A (solvothermal method)
[0159] Weigh 20.8 mg of compound YZG-331 solid and place it in a 3 ml glass vial, add 1 ml of methyl tert-butyl ether, put the 3 ml vial into a hydrothermal reactor with a Teflon liners, place the reactor in a biochemical incubator for temperature rise and fall (temperature program: from 25 ° C to 80 ° C within 6 hours, keep constant temperature at 80 ° C for 12 hours, and reduce to 5 ° C at a rate of 0.05 ° C / min), and then keep it at a constant temperature of 5 ° C.
[0160] After testing, the solid obtained in the above example is Form A. The X-ray powder diffraction data of the obtained solid are shown in Table 9.
[0161] Table 9
[0162]
[0163]
[0164] Examples 11-19: Preparation of Form A1 (Anti-solvent Addition Method)
[0165] Weigh about 20 mg of compound YZG-331 solid and place it in a 20 ml glass vial, add the corresponding volume of positive solvent, and filter the sample solution into a new 20 ml glass vial using a polytetrafluoroethylene filter with a pore size of 0.45 microns. Then, magnetically stir the obtained clear solution (speed of about 1000 rpm), and add the corresponding anti-solvent dropwise thereto. If solid precipitates, centrifuge the obtained solid. If the solution is clear, transfer to 5°C for suspension stirring.
[0166] The detailed experimental conditions involved in the above examples are shown in Table 10. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 15 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 11.
[0167] Table 10
[0168]
[0169] Table 11
[0170]
[0171]
[0172] Examples 20-26: Preparation of Form A1 (Gas-Solid Diffusion Method)
[0173] Weigh about 20 mg of compound YZG-331 solid and place it in a 3 ml glass vial. Pipette 4 ml of solvent into a 20 ml glass vial. Place the 3 ml glass vial containing the solid sample in the 20 ml glass vial with the lid open. Tighten the cap of the 20 ml glass vial and place it at room temperature.
[0174] The detailed experimental conditions involved in the above examples are shown in Table 12. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 23 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 13.
[0175] Table 12
[0176]
[0177]
[0178] Table 13
[0179] Diffraction angle 2θ d value Relative Strength % 6.7 13.2 95.1 8.6 10.3 34.2 11.5 7.7 90.8 12.0 7.5 1.0 12.7 6.9 76.9 13.3 6.6 25.6 14.4 6.2 100.0 15.8 5.6 29.9 17.1 5.2 12.5 17.4 5.1 12.9 17.7 5.0 56.5 18.5 4.8 92.6 19.8 4.5 7.2 20.8 4.3 72.0 22.5 3.9 26.5 22.8 3.9 6.6 24.0 3.7 34.9 24.2 3.7 39.9 24.7 3.6 24.3 26.5 3.4 13.6 26.9 3.3 9.5 27.8 3.2 7.9 29.1 3.1 5.2 29.5 3.0 4.8 31.3 2.9 7.3 32.6 2.7 6.9 33.7 2.7 4.9 35.0 2.6 8.4
[0180] Examples 27-30: Preparation of Form A1 (slow evaporation method)
[0181] Weigh about 20 mg of compound YZG-331 solid into a 3 ml glass vial, add the corresponding volume of solvent, and filter the sample solution into a new 3 ml glass vial using a 0.45 μm pore size polytetrafluoroethylene filter. Seal the 3 ml glass vial with a sealing film, poke 4 small holes in the sealing film, and place it at room temperature to evaporate until solid precipitates.
[0182] The detailed experimental conditions involved in the above examples are shown in Table 14. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 28 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 15.
[0183] Table 14
[0184]
[0185]
[0186] Table 15
[0187] Diffraction angle 2θ d value Relative Strength % 6.6 13.3 100.0 8.5 10.4 1.0 11.5 7.7 31.9 12.7 7.0 3.5 13.3 6.7 60.2 14.3 6.2 7.4 17.1 5.2 0.7 17.6 5.0 29.0 18.4 4.8 12.3 20.7 4.3 16.7 23.1 3.8 1.6 23.8 3.7 3.8 24.1 3.7 26.0 24.7 3.6 7.9 26.4 3.4 1.7 26.7 3.3 26.6 27.2 3.3 0.4 29.7 3.0 0.7 30.8 2.9 0.7 31.2 2.9 3.7 33.6 2.7 8.2 34.0 2.6 2.4 37.5 2.4 1.6 39.2 2.3 1.2
[0188] Examples 31-35: Preparation of Form A1 (slow cooling method)
[0189] About 20 mg of compound YZG-331 solid was weighed and placed in a 2 ml glass vial, and the corresponding solvent was added to obtain a suspension. After the suspension was magnetically stirred at 50°C (speed of about 1000 rpm) for about two hours, the sample solution was filtered while hot into a new 2 ml glass vial using a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm, and the temperature was lowered from 50°C to 5°C at a rate of 0.1°C per minute after sealing.
[0190] The detailed experimental conditions involved in the above examples are shown in Table 16. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 32 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 17.
[0191] Table 16
[0192]
[0193] Table 17
[0194]
[0195]
[0196] Examples 36-41: Preparation of Form A1 (gas-liquid permeation method)
[0197] Weigh about 20 mg of compound YZG-331 solid into a 3 ml glass vial, add solvent to dissolve the solid, filter the sample solution into a new 3 ml glass vial using a 0.45 μm pore size polytetrafluoroethylene filter membrane, and place the open vial in a 20 ml glass vial pre-filled with 4 ml of the corresponding anti-solvent. After sealing, place it at room temperature.
[0198] The detailed experimental conditions involved in the above examples are shown in Table 18. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 41 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 19.
[0199] Table 18
[0200]
[0201] Table 19
[0202]
[0203]
[0204] Examples 42-50: Preparation of Form A1 (room temperature suspension stirring method)
[0205] About 20 mg of the solid was weighed and placed in a 2 ml glass vial, and a corresponding volume of solvent was added to obtain a suspension. The suspension was magnetically stirred at room temperature for about 4 days.
[0206] The detailed experimental conditions involved in the above examples are shown in Table 20. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 47 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 21.
[0207] Table 20
[0208]
[0209]
[0210] Table 21
[0211] Diffraction angle 2θ d value Relative Strength % 6.7 13.2 39.9 8.6 10.3 26.9 10.8 8.2 0.0 11.5 7.7 61.0 12.7 7.0 59.9 13.3 6.6 13.9 14.4 6.2 88.4 15.8 5.6 21.8 17.1 5.2 12.3 17.6 5.0 53.9 18.4 4.8 94.9 19.9 4.5 3.8 20.7 4.3 100.0 20.9 4.2 12.5 22.6 3.9 20.4 23.1 3.8 3.4 23.7 3.7 16.2 24.0 3.7 60.3 24.7 3.6 34.5 25.4 3.5 3.9 26.4 3.4 20.0 26.7 3.3 9.4 27.9 3.2 11.2 29.1 3.1 10.8 29.5 3.0 6.7 29.7 3.0 2.1 30.2 3.0 1.7 31.1 2.9 13.1 31.7 2.8 0.0 31.8 2.8 2.8 32.5 2.8 11.1 33.5 2.7 3.8 34.0 2.6 5.3 34.8 2.6 11.8 35.3 2.5 2.9 36.0 2.5 2.3 36.5 2.5 2.1 37.5 2.4 2.6 39.1 2.3 2.7
[0212] Examples 51-59: Preparation of Form A1 (80°C Suspension Stirring Method)
[0213] About 20 mg of compound YZG-331 solid was weighed and placed in a 2 ml glass vial, and a corresponding volume of solvent was added to obtain a suspension. The suspension was magnetically stirred at 80° C. for about 4 days.
[0214] The detailed experimental conditions involved in the above examples are shown in Table 22. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 58 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 23.
[0215] Table 22
[0216]
[0217] Table 23
[0218]
[0219]
[0220] Examples 60-61: Preparation of Form A1 (solvothermal method)
[0221] Weigh about 20 mg of compound YZG-331 solid and place it in a 3 ml glass vial, add the corresponding volume of solvent, put the 3 ml vial into a hydrothermal reactor with a Teflon liner, and place the reactor in a biochemical incubator for temperature rise and fall (temperature program: from 25°C to 80°C within 6 hours, keep constant temperature at 80°C for 12 hours, and reduce to 5°C at a rate of 0.05°C / min), and then keep constant temperature at 5°C. The detailed experimental conditions involved in the above examples are shown in Table 24. After testing, the solids obtained in the above examples are all crystalline form A1. Taking Example 61 as an example, the X-ray powder diffraction data of the obtained solid are shown in Table 25.
[0222] Table 24
[0223]
[0224] Table 25
[0225]
[0226]
[0227] Example 62: Hygroscopicity
[0228] In order to evaluate the hygroscopicity of Form A, the dynamic moisture adsorption-desorption (DVS) curves of Form A and amorphous samples obtained in Preparation Example 1 of the present invention were tested respectively, and the experimental results are shown in Table 26. The DVS of Form A is shown in the attached Fig.10 As shown in the figure. Fig.11 shown.
[0229] Table 26
[0230]
[0231] According to the definition of drug hygroscopicity in the "Chinese Pharmacopoeia 2020 Edition", the crystal form A and crystal form B described in the present invention are both non-hygroscopic or almost non-hygroscopic, and can still maintain stable properties under high humidity conditions. During the production, storage and use, they can remain stable without specific humidity control conditions, and can well meet the requirements of drug production and use.
[0232] Regarding the description of hygroscopic characteristics and the definition of hygroscopic weight gain (Guidelines for hygroscopicity testing of drugs in the 2020 edition of the Chinese Pharmacopoeia):
[0233] Deliquescent: Absorbs enough water to form a liquid
[0234] Highly hygroscopic: weight gain due to moisture absorption is no less than 15%
[0235] Hygroscopic: Weight gain due to moisture absorption is less than 15% but not less than 2%
[0236] Slightly hygroscopic: weight gain due to moisture absorption is less than 2% but not less than 0.2%
[0237] No or almost no hygroscopicity: weight gain due to moisture is less than 0.2%
[0238] Example 63: Comparative Stability Study
[0239] About 20 mg of the crystal form A (initial purity 99.49 area %) and the amorphous sample (initial purity 99.44 area %) obtained in Preparation Example 1 of the present invention were weighed, and the closed mouth was placed in an oven at 80° C., and samples were taken after 1 day to measure the XRPD and HPLC purities; the open mouth was placed in a stabilization box at 25° C. / 60% RH and 40° C. / 75% RH, and samples were taken after 1 week to measure the XRPD and HPLC purities; the closed mouth was placed in a light stabilization box, and the total illumination was: white light 1200000 Lux·hrs+ultraviolet 200W·hrs / m 2 , temperature 25°C, and samples were taken after 1 week to measure XRPD and HPLC purity. The experimental results are shown in Table 27. Form A transformed into amorphous under 40°C / 75%RH conditions, and the crystal form did not change significantly under other conditions. The purity of Form A did not change significantly after being placed under all conditions. The crystal form and purity of the amorphous did not change significantly after being placed under all conditions.
[0240] Table 27
[0241]
[0242] *As a control experiment, a clear glass vial was wrapped with aluminum foil and placed in a light-stable box under the same light conditions.
[0243] Example 64: Solubility of Crystalline Forms
[0244] About 20 mg of the crystal form A and the amorphous sample obtained in Preparation Example 1 of the present invention were weighed, and 2 ml of SGF (simulated gastric juice), FaSSIF (artificial intestinal juice in the fasting state), and FeSSIF (artificial intestinal juice in the fed state) were respectively used to prepare a suspension, and the suspension was filtered after equilibration at 37° C. for 24 hours to obtain a clear solution. The content of the sample in the saturated solution was determined by HPLC. The test results are shown in Table 28.
[0245] About 20 to 40 mg of the crystal form A and the amorphous sample obtained in Preparation Example 1 of the present invention were weighed, and 2 ml of pure water, pH 1.0 buffer, pH 4.5 buffer, and pH 6.8 buffer were used, respectively, and filtered after balancing at room temperature for 24 hours to obtain a clear solution. The content of the sample in the saturated solution was determined by HPLC. The test results are shown in Table 29.
[0246] The experimental results show that in FeSSIF and pH 6.8 buffer, the solubility of form A is higher than that of amorphous form; in FaSSIF, the solubility of amorphous form is higher than that of form A; in SGF, H2O, pH 1.0 and pH 4.5 buffers, there is no significant difference in the solubility of form A and amorphous form.
[0247] Table 28
[0248]
[0249] Table 29
[0250]
[0251] Example 65: Bulk density and tap density of crystal form
[0252] Weigh about 500 mg of the crystal form A and the amorphous sample obtained in Preparation Example 1 of the present invention, add them to a 5 ml measuring cylinder respectively, and record the volume at this time. Tap the measuring cylinder on the table 200 times, and record the volume at this time. Perform three tests in parallel. The test results are shown in Table 30.
[0253] Table 30
[0254]
[0255] Example 66: Angle of repose of crystal form
[0256] Take appropriate amounts of the crystal form A and amorphous sample obtained in Preparation Example 1 of the present invention. Take a funnel and fix it on an iron frame so that it is placed perpendicular to the table. Add the taken crystal form A and amorphous sample into the funnel respectively, and form a cone after free falling. Measure the height and diameter of the cone to calculate the angle of repose. Perform three tests in parallel. The test results are shown in Table 31. The results show that there is no significant difference in the fluidity of the crystal form A and the amorphous sample.
[0257] Table 31
[0258]
[0259] Example 67: Particle Size Distribution Comparative Study
[0260] Weigh appropriate amounts of the crystal form A and amorphous sample obtained in Preparation Example 1 of the present invention, add the dispersion medium ISOPAR G, mix the sample to be tested thoroughly, take 10-30 mg of the sample and add it to the injection system to test the particle size distribution. The test results are shown in Table 32. The crystal form A of the present invention has a unimodal distribution, and the amorphous has a bimodal distribution with a certain overlap.
[0261] Table 32
[0262] Crystal form Volume average particle size (micrometers) D10(micrometer) D50(micrometer) D90(micrometer) Crystalline Form A 57.79 17.95 39.27 122.3 Amorphous 154.8 40.35 132.5 298.2
[0263] Example 68: Contact angle of crystal form
[0264] Weigh appropriate amounts of the crystal form A and the amorphous sample obtained in Preparation Example 1 of the present invention, and test the contact angle of water. Perform two tests in parallel. The test results are shown in Table 33.
[0265] Table 33
[0266] Crystal form Test 1 Test 2 Crystalline Form A 81.5°~84.6° 79.2°~84.6° Amorphous 56.1°~56.8° 54.5°~56.2°
[0267] Example 69: Mechanical stability of the crystal form
[0268] Take appropriate amounts of the crystal form A and the amorphous sample obtained in Preparation Example 1 of the present invention, place them in an agate mortar, grind them manually for about 3 minutes, and then test the crystal form. The test results show that the crystal form A does not undergo a crystal form transformation after grinding, but the crystallinity is slightly reduced, and the amorphous sample is still amorphous.
[0269] Take appropriate amounts of the crystal form A and the amorphous sample obtained in Preparation Example 1 of the present invention, add them to the tablet press, and test the crystal form after tableting at a pressure of 350 MPa. The test results show that the crystal form A does not undergo a crystal form transformation during tableting, but the crystallinity is slightly reduced, and the amorphous sample is still amorphous.
[0270] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. Form A of the compound YZG-331 represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction of the crystalline form A has characteristic peaks at 2θ values of 17.4°±0.2°, 14.1°±0.2°, and 8.4°±0.2°.
2. The crystal form A according to claim 1, has X-ray powder diffraction characteristic peaks at one, two or three of the 2θ values of 18.2°±0.2°, 12.5°±0.2°, and 13.1°±0.2°.
3. The crystalline form A according to any one of claims 1 or 2, wherein the X-ray powder diffraction has characteristic peaks at 2θ values of 18.2°±0.2°, 12.5°±0.2°, and 13.1°±0.2°.
4. The method for preparing the crystalline form A according to any one of claims 1 to 3, characterized in that: The compound of formula (I) is dissolved in at least one of the positive solvents methanol and isopropanol, and after filtering, anti-solvents toluene and cyclohexane are added dropwise thereto. The system is stirred and the temperature is set to rise and fall between 5°C and 50°C for 3 cycles to obtain Form A.
5. The method for preparing the crystalline form A according to any one of claims 1 to 3, characterized in that: The compound of formula (I) is placed in at least one of an atmosphere of methyl tert-butyl ether and toluene, and the solid and the volatile solvent undergo gas-solid diffusion to obtain Form A.
6. The method for preparing the crystalline form A according to any one of claims 1 to 3, characterized in that: The compound of formula (I) is added to methyl tert-butyl ether, and the mixture is sealed with a hydrothermal reactor. The reactor is placed under high temperature and high pressure conditions for reaction, and then the temperature is slowly lowered to 5°C to precipitate a solid, thereby obtaining Form A.
7. The method for preparing the crystalline form A according to any one of claims 1 to 3, characterized in that: An excess amount of the compound of formula (I) is added to a methyl tert-butyl ether system, and the suspension system is stirred at 80° C. to obtain Form A.
8. Form B of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction of the crystalline form B has characteristic peaks at 2θ values of 6.1°±0.2°, 12.2°±0.2°, and 13.7°±0.2°.
9. The crystal form B according to claim 8, wherein the X-ray powder diffraction has characteristic peaks at one, two or three of the 2θ values of 13.3°±0.2°, 17.6°±0.2°, and 6.6°±0.2°.
10. The crystal form B according to any one of claims 8 or 9, wherein the X-ray powder diffraction has characteristic peaks at 2θ values of 13.3°±0.2°, 17.6°±0.2°, and 6.6°±0.2°.
11. The method for preparing the crystal form B according to any one of claims 8 to 10, characterized in that: The compound of formula (I) is added to methyl tert-butyl ether, and the suspension system is stirred at low temperature to obtain Form B.
12. Crystalline Form A1 of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction of the crystalline form A1 has characteristic peaks at 2θ values of 11.6°±0.2°, 14.4°±0.2°, and 6.7°±0.2°; 13. The crystalline form A1 according to claim 12, wherein its X-ray powder diffraction has characteristic peaks at one, two or three of the 2θ values of 18.5°±0.2°, 20.8°±0.2° and 12.8°±0.2°.
14. The crystalline form A1 according to claim 12 or 13, wherein the X-ray powder diffraction has characteristic peaks at 2θ values of 18.5°±0.2°, 20.8°±0.2°, and 12.8°±0.2°.
15. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is dissolved in a positive solvent, filtered, and then an anti-solvent is added dropwise thereto to obtain Form A1.
16. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is placed in a sealed environment containing a solvent, and the solid and the volatilized solvent undergo gas-solid diffusion to obtain Form A1.
17. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is added to an organic solvent or a mixed solvent system, and the suspension system is stirred to obtain the crystalline form A1.
18. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is dissolved in a volatile solvent, evaporated and crystallized to obtain Form A1.
19. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is dissolved in an organic solvent or a mixed solvent system, filtered after reaching a dissolution equilibrium under high temperature conditions, and slowly cooled until solids precipitate to obtain Form A1.
20. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is dissolved in a positive solvent, and then placed in a sealed environment containing an anti-solvent, and crystallized by osmosis to obtain Form A1.
21. The method for preparing the crystalline form A1 according to any one of claims 12 to 14, characterized in that: The compound of formula (I) is added to an organic solvent, and the reaction vessel is sealed with a hydrothermal reactor. The reactor is placed under high temperature and high pressure conditions for reaction, and then the temperature is slowly lowered to 5°C to precipitate a solid, thereby obtaining Form A1.
Citation Information
Patent Citations
N6-substituted Adenosine Derivatives, N6-substituted Adenine Derivatives And Uses Thereof
CN102812033A
N6-substituted adenosine derivative and N6-substituted adenine derivative and application thereof
CN104382924A
Preparation method and uses of N<6>-(1-(4-methoxyphenyl)ethyl)-adenosine
CN105085594A
2,6-diaminopurine derivatives
CN1119440A
Application of N6-substituted adenosine derivative or N6-substituted purine derivative in preparation of medicine for relieving perioperative neuroinflammation
CN117338801A